Angiographic embolization followed by piecemeal resection of giant posterior mediastinal schwannoma: Case report and concise review - Loftus, Tyler J. (Int J Surg Case Rep, 2018)
Introduction: Posterior mediastinal masses present unique diagnostic and therapeutic challenges, particularly when large highly vascularized tumors extend toward or emanate from the spinal cord. The rare nature of these tumors precludes the development of standardized management algorithms, underscoring the importance of case reports. Presentation of case: A 57 year old female presented with exertional dyspnea and right chest pressure. Chest radiography followed by computed tomography (CT) scan demonstrated a 13 cm posterior mediastinal mass involving the T7 vertebral body. CT-guided percutaneous biopsy confirmed benign schwannoma. During open exploration, the tumor bled easily with contact. Angiography with intercostal arterial embolization decreased tumor vascularity while preserving spinal cord perfusion. Subsequent piecemeal resection facilitated exposure of the tumor base and complete resection. Postoperative recovery was uneventful. Discussion: Neurogenic tumors are most commonly located in the posterior mediastinum. When untreated, schwannomas continue to grow, and will inevitably cause compressive symptoms if given sufficient time. Therefore, resection is recommended. This may be performed thoracoscopically in select patients with small tumors, avoiding the morbidity of a thoracotomy incision. Conclusion: Large posterior mediastinal schwannomas require posterolateral thoracotomy and resection. Preoperative angiography helps identify arteries shared by the tumor and the spinal cord, and embolization may reduce tumor vascularity and operative blood loss thereby permitting safer resection.